Analysis of the Use of Interactive Learning Media in Students In the Department of MPLB UPT SMK Negeri 1 Bulukumba - Indri Lestari; Jamaluddin Jamaluddin; Sitti Hardiyanti Arhas (Journal of Educational Development and Learning (JEDAL), 2025)
Analysis of the use of Interactive learning media in students in the MPLB department of UPT SMK Negeri 1 Bulukumba is the ability of students to use learning media selected by teachers interactively. This study aims to determine how the use of interactive learning media in students in the MPLB department of UPT SMKN 1 Bulukumba with a qualitative research type. Therefore, to achieve the objectives of this study, the method used to collect data is by conducting observations, interviews, and documentation. The results of this study indicate that all indicators used in this study can be categorized as less than optimal in their use. The indicators in question are effective in the use of learning media because they can help students' understanding, especially by using LCDs and visual displays. The use of the media is also efficient, especially the readiness of teachers in preparing simple media before class starts. However, the media used is still less varied/diverse which is still dominated by traditional media and printed books which causes a lack of creativity in learning. Thus, this also has an impact on the lack of interactive use of learning media because the use of media is monotonous and does not utilize interactive technology. Traditional media tends to produce one-way communication, which has an impact on low active student participation. The new finding in this study is adaptability, which is also an indicator that plays a role in the use of learning media in this research locus, which is different from the theory used so that it can be used as evaluation material and new findings in the educational environment.